MOTOR COORDINATION, VISUAL FUNCTION AND FUNCTIONAL/ SENSORY VISION TRAINING SYSTEM FOR VOLLEYBALL SPORT - Khaupshev, M.Kh.; Bazhev, A.Z.; Bazhev, A.A.; Musakaev, V.M. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to test and analyze benefits of a new visual function / motor coordination training system for volleyball players. Methods and structure of the study. We run a yearly test of the visual function / motor coordination training equipment at volleyball sports schools of Kabardino-Balkarian State University and Kabardino-Balkarian State Agrarian University. We sampled for the tests the 9-10 to 19-20 year-old volleyball players (n=208) split up into six Reference Groups (RG) and six Experimental Groups (EG). The sample progress was tested by the direct/ feedback visual function and technical and tactical action accuracy tests. Results and conclusion. Special trainings have proved to contribute up to 30-50% in the visual function / functional vision progress, although the traditional training systems never offer training equipment with a feedback capacity for the data flow accuracy control. The experimental visual function / motor coordination training system for volleyball players was tested highly beneficial for harmonized motor coordination / visual function progress in the Experimental group versus the traditional training system. The new training technology effectively facilitated the visual function / technical and tactical action progress as verified by the individual progress profiles and databases. We recommend the new visual function / motor coordination training system and test data for application in volleyball training service.